Prove $$\det(e^A) = e^{\operatorname{tr}(A)}$$ for all matrices $A \in \mathbb{C}_{n×n}$.

  • $\begingroup$ All the answers so far use a triangularized form at some point. If you know that every complex square matrix is triangularizable, it brings the problem back to triangular matrices. $\endgroup$
    – Julien
    Mar 6, 2013 at 16:04

4 Answers 4


Both sides are continuous. A standard proof goes by showing this for diagonalizable matrices, and then using their density in $M_n(\mathbb{C})$.

But actually, it suffices to triangularize $$ A=P^{-1}TP $$ with $P$ invertible and $T$ upper-triangular. This is possible as soon as the characteristic polynomial splits, which is obviously the case in $\mathbb{C}$.

Let $\lambda_1,\ldots,\lambda_n$ be the eigenvalues of $A$.

Observe that each $T^k$ is upper-triangular with $\lambda_1^k,\ldots,\lambda_n^k$ on the diagonal. It follows that $e^T$ is upper triangular with $e^{\lambda_1},\ldots,e^{\lambda_n}$ on the diagonal. So $$ \det e^T=e^{\lambda_1}\cdots e^{\lambda_n}=e^{\lambda_1+\ldots+\lambda_n}=e^{\mbox{tr}\;T} $$

Finally, observe that $\mbox{tr} \;A=\mbox{tr}\;T$, and that $P^{-1}T^kP=A^k$ for all $k$, so $$P^{-1}e^TP=e^A\qquad \Rightarrow\qquad \det (e^T)=\det (P^{-1}e^TP)=\det(e^A).$$

  • $\begingroup$ Nice answer (+1) $\endgroup$
    – Thomas
    Mar 6, 2013 at 16:09
  • 1
    $\begingroup$ @1015 Is it possible to generalize this to $det(f(A))=f(trA)$. Where $f(A)$ is some continuous differentiable function. i.e. use $P^{-1}T^kP=T^k$ in connection with the Taylor expansion of the function $f$. $\endgroup$ Nov 18, 2017 at 15:21

Hint: Use that every complex matrix has a jordan normal form and that the determinant of a triangular matrix is the product of the diagonal.

use that $\exp(A)=\exp(S^{-1} J S ) = S^{-1} \exp(J) S $

And that the trace doesn't change under transformations.

\begin{align*} \det(\exp(A))&=\det(\exp(S J S^{-1}))\\ &=\det(S \exp(J) S^{-1})\\ &=\det(S) \det(\exp(J)) \det (S^{-1})\\ &=\det(\exp (J))\\ &=\prod_{i=1}^n \exp(j_{ii})\\ &=\exp(\sum_{i=1}^n{j_{ii}})\\ &=\exp(\text{tr}J) \end{align*}

  • $\begingroup$ Can i have another hint. its a hard question $\endgroup$
    – John
    Mar 6, 2013 at 15:29
  • $\begingroup$ posted antoher hint $\endgroup$ Mar 6, 2013 at 15:33
  • $\begingroup$ is ta tthe jordan normal form $\endgroup$
    – John
    Mar 6, 2013 at 15:33
  • $\begingroup$ $A$ is the normal matrix and $D$ is the jordan normal form of $A$ $\endgroup$ Mar 6, 2013 at 15:33
  • $\begingroup$ Posted a more explizit proof $\endgroup$ Mar 6, 2013 at 15:40

Let $f(t)= \det(e^{tA})$. Then $f'(t)=D \det(e^{tA}) \cdot Ae^{tA}=\text{tr} \left(^t \text{com}(e^{tA})Ae^{tA} \right)$. But $A$ and $e^{tA}$ commute, and $^t\text{com}(e^{tA})e^{tA}=\det(e^{tA}) \operatorname{I}_n$. Therefore, $f'(t)=\text{tr}(A)f(t)$ and $f(0)=1$, hence $f(t)=e^{\text{tr}(A)t}$. For $t=1$, $\det(e^{A})= e^{\text{tr}(A)}$.

  • $\begingroup$ Ah! Finally an elementary answer...+1. I think you want $com(e^{sA})^te^{sA}=\det(e^{sA})I_n$. $\endgroup$
    – Julien
    Mar 6, 2013 at 16:18
  • $\begingroup$ @julien: Thank you, I edited my answer. $\endgroup$
    – Seirios
    Mar 6, 2013 at 16:52
  • $\begingroup$ Why $D \det(e^{tA}) \cdot Ae^{tA}=\text{tr} \left(^t \text{com}(e^{tA})Ae^{tA} \right)$? $\endgroup$
    – math.n00b
    Aug 16, 2014 at 14:44
  • $\begingroup$ The result is known as Jacobi's formula: en.wikipedia.org/wiki/Jacobi's_formula $\endgroup$
    – Seirios
    Aug 16, 2014 at 15:17

You can do it in these steps (still requires some work):

$\quad \bf (1)$ $A$ is diagonalizable

$\quad \bf (2)$ $A$ is nilpotent

$\quad \bf (3)$ $A$ is arbitrary

$\bf (1)$ This shouldn't be too hard. Start with assuming that $A = CDC^{-1}$ for $D$ a diagonal matrix.

$\bf (2)$ Use that every nilpotent matrix is similar to a upper triangular matrix $D$ with $0$s on the diagonal. So $A = CDC^{-1}$.

$\bf (3)$ Use that every matrix can be written as the sum $A = D + N$ of a nilpotent matrix $N$ and a diagonalizable matrix $D$ and $D$ and $N$ commute. So $$ \det(e^{A}) = \det(e^De^N) =\det(e^{D})\det(e^{N}) = e^{\text{Tr}(D)}e^{\text{Tr}(N)} = e^{\text{Tr}(D) + \text{Tr}(N)} = e^{\text{Tr}(A)}. $$ We have used here that $D$ and $N$ commute so that $e^A = e^De^N.$

  • $\begingroup$ so is this basically all i need to write out $\endgroup$
    – John
    Mar 6, 2013 at 15:38
  • $\begingroup$ @John: Yes. But you still have to write down the details of step (1) and (2) and there was some claims that I assumed you know. $\endgroup$
    – Thomas
    Mar 6, 2013 at 15:39
  • $\begingroup$ can you help me a bit more please regarding those details $\endgroup$
    – John
    Mar 6, 2013 at 15:40
  • $\begingroup$ @John: What specific details? (Left is really just to write things down. For example, for step (1) try and write down a diagonal matrix $D$ and the figure out what $e^D$ is using that definition of the exponential map. $\endgroup$
    – Thomas
    Mar 6, 2013 at 15:42
  • 1
    $\begingroup$ @julien: I like the idea of step (3). I guess it seems more clear to me... $\endgroup$
    – Thomas
    Mar 6, 2013 at 16:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.